Skeletal and dentoalveolar effects of Twin-block and bionator appliances in the treatment of Class II malocclusion: A comparative study - Jena, Ashok Kumar; Duggal, Ritu; Parkash, Hari (American journal of orthodontics and dentofacial orthopedics, 2006)
Introduction: The purpose of this study was to evaluate the skeletal and dentoalveolar effects of the Twin-block and bionator appliances in the treatment of Class II Division 1 malocclusions. Methods: Fifty-five girls from North India with Class II Division 1 malocclusion and the same physical growth maturation status were selected for the study. The subjects were divided among a Twin-block group (n = 25), a bionator group (n = 20), and a control group (n = 10). Pretreatment and posttreatment lateral cephalometric radiographs of the treatment group subjects, and prefollow-up and postfollow-up radiographs of the control group subjects, were traced manually and subjected to the pitchfork analysis. Results: Statistical software was used for 1-way analysis of variance and multiple comparisons (post-hoc test, Bonferroni). A P value of .05 was considered statistically significant. Neither the Twin-block nor the bionator appliance significantly restricted forward growth of the maxilla ( P = .476). Mandibular growth in the Twin-block subjects was significantly greater than in controls ( P = .005). Mandibular growth was comparable in the control and the bionator subjects. Molar correction, overjet reduction, and proclination of the mandibular incisors were significantly greater ( P = .000) in the treated subjects compared with the controls. Conclusions: Both the Twin-block and bionator appliances were effective in correcting molar relationships and reducing overjets in Class II Division 1 malocclusion subjects. However, the Twin-block was more efficient than the bionator in the treatment of Class II Division 1 malocclusion.